(untitled) (Journal of Medical & Health Sciences Review, 2025)
Refractive errors, pre-presbyopia, and asthenopic symptoms are common among individuals engaged in prolonged near work without regulated working hours. • Refractive error refers to a visual condition in which parallel rays of light entering the eye fail to focus precisely on the retina, instead coming to a focus either in front of it, behind it, or at multiple focal points. • Asthenopia (eye strain) is characterized by symptoms such as headache, nausea, vomiting, ocular discomfort, and blurred vision, often triggered by sustained visual tasks. • Pre-presbyopia describes the early onset of near vision difficulties before the age of 40 years, usually due to premature decline in accommodative function. Purpose: To determine the prevalence of early-onset presbyopia and asthenopic symptoms, and to identify associated visual and environmental risk factors among informal handcraft workers in Pakistan. Methods:A community-based cross-sectional study was conducted among 100 informal handcraft workers (50 males, 50 females), aged 16–35 years, from Kot Qaisrani village (Dera Ghazi Khan) and Hussaina Gahi Bazaar (Multan). Assessments included visual acuity (logMAR charts), refractive status (retinoscopy), convergence (pencil push-up test), and asthenopic symptoms (structured questionnaire). Chi-square tests were applied to evaluate associations between symptoms and potential risk factors. Results: • Early-onset presbyopia: Prevalence 30% (N8–N12 near acuity). • Asthenopia: Eye strain reported by 64%, significantly associated with reduced near vision (p = 0.052) and prolonged working hours. • Convergence insufficiency: Present in 48%, strongly correlated with asthenopic symptoms. • Headache: Reported by 72%, significantly associated with poorer near vision (p = 0.008). • Refractive errors: 17% myopic, 9% hyperopic, 74% emmetropic. • Near visual acuity: 70% N6, 17% N8, 13% N10–N12. • Work conditions: 51% worked 9–12 hours/day, 91% reported insufficient rest, and 56% lacked adequate lighting. • Eye care access: Only 20% had ever visited an eye care professional; 19% self-medicated with eye drops. Early-onset presbyopia and asthenopic symptoms are highly prevalent among young handcraft workers. Major contributing factors include prolonged near work, poor lighting, lack of regular breaks, and convergence insufficiency. Preventive strategies—such as workplace ergonomic modifications, regular vision screening, and improved access to eye care—are urgently required to protect long-term ocular health in this vulnerable population.